Educative game tool reduces the pre-operation of anxiety in school age children - Harmilah Harmilah; Kristina Weningtyastuti; Yustiana Olfah (Jurnal Kesehatan Ibu dan Anak, 2021)
Educational game tools can be an appropriate educational method for children because it can create exciting play situations  to reduce anxiety on pre-operative in school age children. The objective was to found out the effect of educational game tools   on preoperative anxiety in school-age children. The type of study was quasy experimental study with pre-post-test with control group design. The sampling technique was consecutive sampling with 34 patients. The result of pre-test anxiety in intervention group was dominated by medium anxiety as many as 9 people (52.9%), severe anxiety were 6 people (35.3%), and mild anxiety were 2 people (11.8%). The post-test results showed a decrease in anxiety, mild anxiety by 10 people (58.8%) and moderate anxiety by 7 people (41.2%). The Man Whitney test was obtained  that there was an influence of providing educational game to preoperative anxiety in school-age children (p-value=0.000). Educational game tool has decreased preoperative anxiety in school-age children.